Easy computer basics - Miller, Michael, 1958- (Que ; Pearson Education [distributor], 2005)
Your new PC just arrived. You open the box, excited to hook it up, start surfing the web, send e-mails...and then you see all of the cords, CD-ROMs and parts that need to be connected and installed, and suddenly it doesn't seem like so much fun anymore. The instructions look even more intimidating. Don't panic! Easy Computer Basics can help. This up-to-date, full-color, highly visual guide will walk you through the entire set-up process and then show you how to use the different programs to accomplish common tasks. You'll learn how to: Use Microsoft Windows, Works and Word Connect to the Internet Surf the web Read and write e-mail View and edit digital pictures Download and listen to digital music Add new devices, such as printers and hard drives Perform basic maintenance and security tasks Having a computer is supposed to be fun, so don't let its size or complexity take the fun out of your experience. Make your PC work for you with Easy Computer Basics .